Inclusion in and through disability sport? A scoping review using the examples of goalball and wheelchair basketball - Felix Oldörp; Christopher Mihajlovic; Martin Giese (JSAMS Plus)
Background: Inclusion in sport has been empirically investigated and demonstrated the potential for promoting inclusion. Nevertheless, a comprehensive overview of how inclusion is understood and theoretically conceptualized within the context of disability sports research is still lacking. Therefore, a scoping review has been conducted to map the existing literature concerning the conceptions of inclusion in disability sports using goalball and wheelchair basketball as examples. Methods: For the scoping review a comprehensive search of five databases was conducted, resulting in the identification of nine articles that were deemed eligible for review. Coding of the data was performed to categorize specific elements, aiming to identify key features and concepts related to inclusion. Results: All reviewed articles recognize sport as an environment in which people of all (dis)abilities can participate. Abilities acquired in and through sport were presented as an important element for inclusion. Inclusion concepts in the articles were based on different concepts. But the concepts were not always clearly defined. In the qualitative studies analyzed, the concepts of inclusion were expanded to include subjective feelings such as equality and belonging based on the statements of the participants. Conclusions: The findings highlight the need for further research using qualitative methodologies that extend beyond the spatial dimension of inclusion, encompassing other dimensions to provide a more comprehensive understanding of inclusion in (disability) sport. Since discussions about inclusion concepts have been primarily driven by physical education research, future research should also focus on recreational and popular sports to strengthen inclusive sports programs.